2013
DOI: 10.2478/raon-2013-0044
|View full text |Cite
|
Sign up to set email alerts
|

Usability application of multiplex polymerase chain reaction in the diagnosis of microorganisms isolated from urine of patients treated in cancer hospital

Abstract: Background. The objective of this study was: i) to compare the results of urine culture with polymerase chain reaction (PCR) -based detection of microorganisms using two commercially available kits, ii) to assess antimicrobial susceptibility of urine isolates from cancer patients to chosen antimicrobial drugs and, if necessary, to update the recommendation of empirical therapy. Materials and methods. A one-year hospital-based prospective study has been conducted in Greater Poland Cancer Centre and Genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Although PCR can uniformly provide faster identification of pathogens, it is also subject to identifying pathogens that are either present in inconsequential amounts in the urine or a part of the patient’s urinary microbiome [ 38 ]. Additionally, while identification of the causative organism helps tailor antimicrobial treatment, most PCR results are unable to provide information regarding sensitivity of the pathogens to different treatments, unlike the standard urine culture [ 46 ]. Currently, the detection of antibiotic resistance in bacteria present in urine is limited to a handful of known resistance genes [ 46 ], or a more robust investigation of several treatment resistance-associated genes in multiplex PCR testing of a single family of bacteria such as Enterobacteriaceae [ 47 ].…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although PCR can uniformly provide faster identification of pathogens, it is also subject to identifying pathogens that are either present in inconsequential amounts in the urine or a part of the patient’s urinary microbiome [ 38 ]. Additionally, while identification of the causative organism helps tailor antimicrobial treatment, most PCR results are unable to provide information regarding sensitivity of the pathogens to different treatments, unlike the standard urine culture [ 46 ]. Currently, the detection of antibiotic resistance in bacteria present in urine is limited to a handful of known resistance genes [ 46 ], or a more robust investigation of several treatment resistance-associated genes in multiplex PCR testing of a single family of bacteria such as Enterobacteriaceae [ 47 ].…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…Additionally, while identification of the causative organism helps tailor antimicrobial treatment, most PCR results are unable to provide information regarding sensitivity of the pathogens to different treatments, unlike the standard urine culture [ 46 ]. Currently, the detection of antibiotic resistance in bacteria present in urine is limited to a handful of known resistance genes [ 46 ], or a more robust investigation of several treatment resistance-associated genes in multiplex PCR testing of a single family of bacteria such as Enterobacteriaceae [ 47 ]. Schmidt et al, suggest that this admittedly limited capability of PCR testing may still offer clinicians the ability to guide treatment decisions early in the disease course by including genes commonly associated with drug-resistance in urinary pathogens.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…9 Few studies have compared multiplex PCR with urine culture for diagnosis of UTIs and acute cystitis. Although several studies have compared performance of PCR with urine culture for detection of a single pathogen, only 4 have tested multiplex PCR: one against 15 bacteria, 10 a second against 14 bacteria together with 6 fungi, 11 a third against 20, 12 and the fourth against 9 bacteria. 13 Polymicrobial infections may occur in as many of 39% of UTIs 14,15 and can display enhanced virulence and increased antibiotic resistance.…”
mentioning
confidence: 99%
“…The presence of multiple strains of bacteria in urine is a recent finding of unknown significance, made possible only by the extreme sensitivity of RT-qPCR. Cybulski et al 17 found a similarly high number of mixed infections in a study evaluating the performance of multiplex PCR on 72 positive urine cultures from adult oncology patients. While E coli and Enterococcus spp were the most common in that study, E coli and P vulgaris were the most commonly identified in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…Numerous studies have validated the utility of PCR-based methodologies for the rapid identification of uropathogens in adult patients, however there have been no similar investigations in pediatric patients. [12][13][14][15][16][17]…”
Section: Introductionmentioning
confidence: 99%